STRATEGI MEMBANGUN KOMUNIKASI YANG EFEKTIF UNTUK MENINGKATKAN KINERJA GURU DI SEKOLAH - Suriya Jaya (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2021)
This article aims to reveal: (1) the nature of communication in the perspective of the Qur'an, (2) the meaning of communication in organizations according to experts, (3) the nature and benefits of effective communication for school/madrasah principals, (4) indicators of effective communication in school/madrasah, (5) the nature of teacher performance in school, (6) the principal's strategy to build effective communication to improve teacher performance in school/madrasah.